Photography and Other Media in the Nineteenth Century - Natale, Simone, 1981-; Leonardi, Nicoletta (Book collections on Project MUSE., 2018)
"A collection of essays investigating photography's role in the evolution of media and communication in the nineteenth century"--Provided by publisher